Positive running, a model for high speed running - Bosch, F. (IFAC, 2013)
Autor writes about • positive running posture sums up the right technique for top speed, • building blocks in running: Pelvic rotation for- and backward and hamstring function, • control of anterior-posterior pelvic rotation is crucial for hamstring function, • ground-reaction-force and the whip from the hip.